2008
DOI: 10.1258/jtt.2008.080104
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a home-based telerehabilitation system compared to usual care: arm/hand function in patients with stroke, traumatic brain injury and multiple sclerosis

Abstract: We conducted a randomized controlled multicentre trial to investigate the feasibility of a telerehabilitation intervention for arm/hand function (the Home Care Activity Desk [HCAD] training) in a home setting. Usual care was compared to HCAD training. The hypothesis was that the clinical outcomes of the HCAD intervention would be at least the same as those measured after a period of usual care for patients with stroke, traumatic brain injury (TBI) and multiple sclerosis (MS) with respect to their arm/hand func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
148
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(152 citation statements)
references
References 20 publications
1
148
0
3
Order By: Relevance
“…The results of these yielded ambiguous results. [21][22][23][24][25] In particular, the results from two systematic reviews, 24,25 which were both negative, may be problematic to interpret largely due to the variability in treatment contrasts. Interventions provided in the included studies, 7 and 10, respectively, were delivered by virtual reality, phone, and internet-based therapies.…”
Section: Section 2: Organization Of Telestroke Services For Ongoing Smentioning
confidence: 99%
“…The results of these yielded ambiguous results. [21][22][23][24][25] In particular, the results from two systematic reviews, 24,25 which were both negative, may be problematic to interpret largely due to the variability in treatment contrasts. Interventions provided in the included studies, 7 and 10, respectively, were delivered by virtual reality, phone, and internet-based therapies.…”
Section: Section 2: Organization Of Telestroke Services For Ongoing Smentioning
confidence: 99%
“…5 However, the strength of evidence is low, with much of the data drawn from case series, 6,7 or feasibility studies. 8,9 A recent Cochrane review of telerehabilitation services for stroke concluded that there is insufficient evidence to guide practice. 10 Applications of telerehabilitation in the domain of aphasia are even more preliminary.…”
Section: Introductionmentioning
confidence: 99%
“…A high completion rate across all the included studies was noted. The greatest participant dropout rate was in Huijgen et al [38], which lost 11 out of 81 participants (13.58%), however this was a mixed sample of participants and it was not reported whether the participants who dropped out had a diagnosis of MS, traumatic brain injury or stroke. Detailed information of the included studies' interventions is presented in Supplementary Table 1 in the appendix.…”
Section: Considering the Summary Of Included Studiesmentioning
confidence: 97%